2016
DOI: 10.1007/s00204-016-1899-0
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA methylation profiling of manganese-exposed human neuroblastoma SH-SY5Y cells reveals epigenetic alterations in Parkinson’s disease-associated genes

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 57 publications
(2 reference statements)
1
21
0
Order By: Relevance
“…Alternatively, or in addition, these lasting protein level changes may be mediated via epigenetic mechanisms, given that expression of several of them (e.g., TH, D2, DAT, and NET) are in part epigenetically regulated via DNA methylation (Archer, Berman, & Blum, ; Day et al, ; Groleau et al, ; Hillemacher et al, ) . This latter suggestion is supported by several studies in human neuroblastoma SH‐SY5Y cells showing that Mn exposure led to hypermethylated TH promoter and down‐regulated TH gene transcription (Gandhi, Sivanesan, & Kannan, ; Tarale et al, ). Recent evidence has also shown that TH expression can be mediated in part by the activity of c‐RET kinase, and that human neuroblastoma cells exposed to 30 µM Mn experienced a c‐RET mediated reduction in TH (Kumasaka et al, ).…”
Section: Discussionmentioning
confidence: 67%
“…Alternatively, or in addition, these lasting protein level changes may be mediated via epigenetic mechanisms, given that expression of several of them (e.g., TH, D2, DAT, and NET) are in part epigenetically regulated via DNA methylation (Archer, Berman, & Blum, ; Day et al, ; Groleau et al, ; Hillemacher et al, ) . This latter suggestion is supported by several studies in human neuroblastoma SH‐SY5Y cells showing that Mn exposure led to hypermethylated TH promoter and down‐regulated TH gene transcription (Gandhi, Sivanesan, & Kannan, ; Tarale et al, ). Recent evidence has also shown that TH expression can be mediated in part by the activity of c‐RET kinase, and that human neuroblastoma cells exposed to 30 µM Mn experienced a c‐RET mediated reduction in TH (Kumasaka et al, ).…”
Section: Discussionmentioning
confidence: 67%
“…Regarding PD risk, gene activity of PARK2 and PINK1 was altered via DNA hypermethylation in dopaminergic human neuroblastoma SH-SY5Y cells upon Mn exposure (Tarale et al, 2016). Furthermore, mice exposed to MnCl 2 showed DNA hypo- and hypermethylation of different loci in substantia nigra (Yang et al, 2016).…”
Section: Other Nutritional/environmental Factors and Dna Methylationmentioning
confidence: 99%
“…The precise cause of Parkinson's disease (PD) remains unknown; however, recent literature points to mitochondrial dysfunction, chronic inflammation and oxidative stress as the pivotal mechanisms of PD neuropathology [4]. Additionally, environmental risk factors such as carbon disulfide, cyanide, herbicides, methanol/organic solvents, pesticides and manganese have been implicated in PD-associated DAergic neuronal cell death [3,5].…”
Section: Introductionmentioning
confidence: 99%